Fluorescence fluctuations and equivalence classes of Ca²⁺ imaging experiments. - Estefanía Piegari; Lucía Lopez; Emiliano Perez Ipiña; Silvina Ponce Dawson (PLoS ONE)
Ca²⁺ release into the cytosol through inositol 1,4,5-trisphosphate receptors (IP₃Rs) plays a relevant role in numerous physiological processes. IP₃R-mediated Ca²⁺ signals involve Ca²⁺-induced Ca²⁺-release (CICR) whereby Ca²⁺ release through one open IP₃R induces the opening of other channels. IP₃Rs are apparently organized in clusters. The signals can remain localized (i.e., Ca²⁺ puffs) if CICR is limited to one cluster or become waves that propagate between clusters. Ca²⁺ puffs are the building blocks of Ca²⁺ waves. Thus, there is great interest in determining puff properties, especially in view of the current controversy on the spatial distribution of activatable IP₃Rs. Ca²⁺ puffs have been observed in intact cells with optical techniques proving that they are intrinsically Ca²⁺ dyes, slow exogenous buffers (e.g., EGTA) to disrupt inter-cluster CICR and UV-photolyzable caged IP3. Single-wavelength dyes increase their fluorescence upon calcium binding producing images that are strongly dependent on their kinetic, transport and photophysical properties. Determining the artifacts that the imaging setting introduces is particularly relevant when trying to analyze the smallest Ca²⁺ signals. In this paper we introduce a method to estimate the expected signal-to-noise ratio of Ca²⁺ imaging experiments that use single-wavelength dyes. The method is based on the Number and rightness technique. It involves the performance of a series of experiments and their subsequent analysis in terms of a fluorescence fluctuation model with which the model parameters are quantified. Using the model, the expected signal-to-noise ratio is then computed. Equivalence classes between different experimental conditions that produce images with similar signal-to-noise ratios can then be established. The method may also be used to estimate the smallest signals that can reliably be observed with each setting.